Digital Storytelling as an Innovative Tool for Improving Academic Writing Skills Among English Major Students: A Mixed-Methods Approach - Ginting, Datulina (Journal of Pedagogy and Education Science, 2025)
This study investigates the effectiveness of digital storytelling as an innovative pedagogical tool for enhancing academic writing skills among English major students in Indonesian higher education. Digital storytelling, which combines traditional narrative techniques with multimedia elements, has emerged as a promising approach to address the challenges students face in developing academic writing competencies. A mixed-methods research design was employed to examine the impact of digital storytelling interventions on students' writing performance, engagement, and skill development. The study involved 60 English major students from a public university in Indonesia, divided into experimental and control groups. Quantitative data were collected through pre- and post-assessment writing tests, while qualitative data were gathered through interviews, focus group discussions, and reflective journals. Results indicated significant improvements in academic writing skills among students who participated in digital storytelling activities compared to those receiving traditional instruction. The findings revealed enhanced narrative competence, improved technological literacy, and increased student motivation and engagement. This research contributes to the growing literature on innovative pedagogical approaches in language education. It provides practical implications for educators seeking to integrate technology-enhanced learning in academic writing instruction.